2018
DOI: 10.7717/peerj.5421
|View full text |Cite
|
Sign up to set email alerts
|

The influence of residual force enhancement on spinal and supraspinal excitability

Abstract: BackgroundFollowing active muscle lengthening, there is an increase in steady-state isometric force as compared with a purely isometric contraction at the same muscle length and level of activation. This fundamental property of skeletal muscle is known as residual force enhancement (RFE). While the basic mechanisms contributing to this increase in steady-state isometric force have been well documented, changes in central nervous system (CNS) excitability for submaximal contractions during RFE are unclear. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 37 publications
6
24
0
Order By: Relevance
“…Contrary to these findings under submaximal contraction intensities, Hahn et al (2012) found larger MEPs, but unchanged CMEPs, following stretch of the plantar flexors during maximal voluntary contractions. Both the results of Hahn et al (2012) and Sypkes et al (2018) could be interpreted as an increase in cortical excitability in the presence of rFE. Further, enlarged V-waves during rFE in the Hahn and colleagues (2012) study suggest a greater motoneuronal output and/or an increase in stretch reflex excitability after active stretch (Hahn et al 2012).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Contrary to these findings under submaximal contraction intensities, Hahn et al (2012) found larger MEPs, but unchanged CMEPs, following stretch of the plantar flexors during maximal voluntary contractions. Both the results of Hahn et al (2012) and Sypkes et al (2018) could be interpreted as an increase in cortical excitability in the presence of rFE. Further, enlarged V-waves during rFE in the Hahn and colleagues (2012) study suggest a greater motoneuronal output and/or an increase in stretch reflex excitability after active stretch (Hahn et al 2012).…”
Section: Introductionmentioning
confidence: 77%
“…Two further studies have used motor evoked potentials (MEPs) and cervicomedullary motor evoked potentials (CMEPs) to investigate modulations to the excitability of cortical and spinal sites in the presence of rFE (Hahn et al, 2012; Sypkes et al, 2018). During submaximal dorsiflexion contractions, Sypkes et al (2018) found unchanged TA MEPs, but reduced TA CMEPs, following active muscle stretch compared with fixed-end reference contractions. This is in line with the idea of reduced motor unit recruitment (Altenburg et al 2008) and might be caused by tension-related afferent feedback as assessed by tendon-evoked inhibitory reflexes (Contento et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations